Age-friendly cities and communities : a global perspective - Buffel, Tine; Handler, Sophie; Phillipson, Chris (Ageing in a global context., 2018)
"As the drive towards creating age-friendly cities grows, this important book provides a comprehensive survey of theories and policies aimed at improving the quality of life of older people living in urban areas. In this book, part of the Ageing in a Global Context series, leading international researchers critically assess the problems and the potential of designing age-friendly environments. The book considers the different ways in which cities are responding to population ageing, the different strategies for developing age-friendly communities, and the extent to which older people themselves can be involved in the co-production of age-friendly policies and practices. The book includes a manifesto for the age-friendly movement, focused around tackling social inequality and promoting community empowerment."--